2021
DOI: 10.21203/rs.3.rs-960337/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complex Functional Brain Network Properties in Anorexia Nervosa

Abstract: Background Anorexia nervosa (AN) is a disorder characterized by an incapacitating fear of weight gain and by a disturbance in the way the body is experienced, facets that motivate dangerous weight loss behaviors. Multimodal neuroimaging studies highlight atypical neural activity in brain networks involved in interoceptive awareness and reward processing. Methods The current study used resting-state neuroimaging to model the architecture of large-scale functional brain networks and characterize network proper… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…However, these alterations involve a number of disturbances in the interplay of several different stress-responsive systems that interact centrally and peripherally to produce individualized clinical phenotypes and vulnerabilities. Alterations in functional connectivity have been investigated in separate studies of both PTSD [279][280][281][282] and ED patients [283][284][285][286]. No such studies have yet been reported in ED patients with and without PTSD.…”
Section: Social Conditions / Local Contextmentioning
confidence: 99%
“…However, these alterations involve a number of disturbances in the interplay of several different stress-responsive systems that interact centrally and peripherally to produce individualized clinical phenotypes and vulnerabilities. Alterations in functional connectivity have been investigated in separate studies of both PTSD [279][280][281][282] and ED patients [283][284][285][286]. No such studies have yet been reported in ED patients with and without PTSD.…”
Section: Social Conditions / Local Contextmentioning
confidence: 99%